Graphics' design work / Dayang Aina Maisara Awg Karim - Awg Karim, Dayang Aina Maisara (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The salted Terubok fish, a traditional dish in Sarawak, is the subject matter of the artwork. This artwork analyses the characteristics of salted Terubok fish through the understanding of media dimension. In printmaking, the balance of harmony between brilliant colors and monotone hues serves as the focal point. The texture is highlighted in the sculpture. The Paintings employ contrast and a range of subjects, while drawings depict divided states and precise forms.